131 USE OF FDG-PET BRAIN IMAGING IN THE DIAGNOSIS AND MANAGEMENT OF DEMENTIA IN A UNIVERSITY HOSPITAL. (25th October 2022) - Marks, E; Doyle, K; Magennis, B; O'Connell, M; McGreevy, C
Abstract: Background: Neuroimaging is an increasingly important tool dementia work-up. Subtype diagnosis helps predict the course of the disease, aiding prognostication and management. Amyloid-beta peptide is intrinsic to the pathogenesis of Alzheimer's disease (AD), forming characteristic neuritic plaques which can be imaged in vivo on positron emission tomography (PET) scans. NICE recommendations advise use of PET imaging if dementia sub-type diagnosis is unclear and AD is suspected. We sought to establish the referral patterns for FDG-PET brain scans for patients aged 60 and over in a university hospital and to establish whether this imaging modality contributed to a change in diagnosis or treatment. Methods: Requests for FDG-PET CT brain from 2019 – 2022 were retrospectively reviewed. Information was obtained from clinical notes and patient information software. Patient demographics, indication for scan, source of referral and whether imaging results led to a change in diagnosis or treatment was recorded. Results: A total of 32 patients were reviewed, with a mean age of 65 years (13 females; 41%). We further analysed the 25 who were aged over 60; this subgroup had a mean age of 70 (9 females; 36%). All 25 patients were appropriately referred to assess for dementia subtype. A revision in diagnosis based on PET imaging was made in 17 (68%) cases. In 9 (30%) cases, results prompted change in dementia-specific pharmacological treatment, including donepezil and memantine. A further 6 (24%) had pharmacological treatment for non-cognitive symptoms of dementia adjusted, such as anti-depressants or anti-psychotics. The majority of referrals had come from neurologists (n = 15; 60%) rather than geriatricians (n = 10; 40%). The final diagnosis was AD in 12 cases (48%) and fronto-temporal dementia in 3 cases (12%). Conclusion: PET scans are a useful functional imaging modality which can help to differentiate dementia subtypes and influence management.